Analysis of Financial Performance on Profit Growth (Studies in Pharmaceutical, Telecommunication and Transportation Subsector Companies on the IDX for 2019-2021): Studies in Pharmaceutical, Telecommunication and Transportation Subsector Companies on the IDX for 2019-2021 - Alvina Tiza Tarizky; S Handayani (Universitas Islam Lamongan, 2023)
The purpose of this study was to determine the effect of financial performance analysis on profit growth in pharmaceutical, telecommunication and transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The independent variables used are Working Capital to Total Assets (WCTA), Current Liability to Inventory (CLI), Total Assets Turn Over (TATO), and Net Profit Margin (NPM). While the dependent variable is measured by profit growth. The company’s annual financial statements are a source of secondary data in this study. Classical assumption test, multiple linear regression analysis and hypothesis testing were used to analyze the data. The results showed that Working Capital to Total Assets (WCTA) and Total Assets Turn Over (TATO) had no effect on profit growth. Meanwhile, two other variables, namely Working Current Liability to Inventory (CLI) and Net Profit Margin (NPM) have a negative effect on profit growth.